Non-Optimal Wet-Bulb Temperature and Short-Term Black Carbon Exposure Largely Impact Emergency Department Visits for Cause-Stable Ischemic Heart Disease - Qianrong Chen; Kun Hou; Xia Xu; Zhen Wang (Atmosphere)
Little is known about the effects of wet-bulb temperature (WBT) and short-term black carbon (BC) exposure on emergency department visits for cause-stable ischemic heart disease (CSIHD). In this study, we improved and extended a set of distributed lag nonlinear models (DLNMs). After controlling for the interaction effect of WBT and BC and multiple confounding factors, we found that the lagged effect of low WBT reached the maximum risk of 1.076 (95% CI, 1.083–1.134) at lag day 7, which was greater than the maximum value of 1.057 (95% CI, 1.016–1.093) of high WBT occurring at lag day 0. The lagged effects of low and high BC both approached their maximum at lag day 0, corresponding to the risk of 1.061 (95% CI, 1.021–1.085) and 1.326 (95% CI, 1.072–1.187), respectively. The effect of short-term consecutive extreme low WBT was significant over a duration of 0–5.5 days and became insignificant after 5.5 days, whereas extreme high WBT had no impact except for the duration of 0–3 days. Exposure to short-term consecutive extreme low and high BC was found to have significant effects over a certain period, manifested in the durations of 0–1, 4–10, and 0–10 days, respectively. Our study confirmed the association of varying degrees of WBT and BC with emergency department visits for CSIHD, and targeted public health interventions for individuals are recommended under specific external humid thermal and high air pollution environments.